Effect of discrete fibre reinforcement on soil tensile strength - Jian Li (Journal of Rock Mechanics and Geotechnical Engineering, 2014)
The tensile behaviour of soil plays a significantly important role in various engineering applications. Compacted soils used in geotechnical constructions such as dams and clayey liners in waste containment facilities can suffer from cracking due to tensile failure. In order to increase soil tensile strength, discrete fibre reinforcement technique was proposed. An innovative tensile apparatus was developed to determine the tensile strength characteristics of fibre reinforced soil. The effects of fibre content, dry density and water content on the tensile strength were studied. The results indicate that the developed test apparatus was applicable in determining tensile strength of soils. Fibre inclusion can significantly increase soil tensile strength and soil tensile failure ductility. The tensile strength basically increases with increasing fibre content. As the fibre content increases from 0% to 0.2%, the tensile strength increases by 65.7%. The tensile strength of fibre reinforced soil increases with increasing dry density and decreases with decreasing water content. For instance, the tensile strength at a dry density of 1.7 Mg/m3 is 2.8 times higher than that at 1.4 Mg/m3. It decreases by 30% as the water content increases from 14.5% to 20.5%. Furthermore, it is observed that the tensile strength of fibre reinforced soil is dominated by fibre pull-out resistance, depending on the interfacial mechanical interaction between fibre surface and soil matrix.